2013
DOI: 10.1148/radiol.13122242
|View full text |Cite
|
Sign up to set email alerts
|

The 100 Most-cited Articles in the Imaging Literature

Abstract: Preclinical articles, primarily in the field of neurologic MR imaging, were highly represented in the top 100 cited articles in the medical imaging literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 21 publications
(21 reference statements)
6
44
1
Order By: Relevance
“…The 100 most cited articles on oral cancer were published in scientific journals with a high IF, and the majority of which were in the first quartile for their category. Thus, a significant number of studies were concentrated in a limited nucleus of journals, as has been observed in other bibliometric reviews; this phenomenon is known as Bradford's law . Authors are attracted to journals with a higher IF, as studies published in such journals will presumably receive a larger number of citations, thus maintaining the IF of the journals.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The 100 most cited articles on oral cancer were published in scientific journals with a high IF, and the majority of which were in the first quartile for their category. Thus, a significant number of studies were concentrated in a limited nucleus of journals, as has been observed in other bibliometric reviews; this phenomenon is known as Bradford's law . Authors are attracted to journals with a higher IF, as studies published in such journals will presumably receive a larger number of citations, thus maintaining the IF of the journals.…”
Section: Discussionmentioning
confidence: 82%
“…The time factor has a clear influence on citation analysis. Recently published articles are at a disadvantage and could be underrated with regard to their scientific impact as they have had less time to accumulate citations . In contrast, the oldest articles may have a high number of citations independently of their current impact…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It not only allows the evaluation of research performance, but also helps investigators refine their research blueprint based on the research trends and overall landscape of the research field (Brinjikji et al, 2013; Yeung et al, 2017a). There are already numerous reports that identified the 100 most cited articles, also known as citation classics, in various fields such as imaging (Brinjikji et al, 2013), radiology (Yoon et al, 2013; Pagni et al, 2014), neuroimaging (Kim et al, 2016), neurosurgery (Ponce and Lozano, 2010), and neurosciences (Yeung et al, 2017a). Analyses based on citation counts are primarily supported by an earlier notion that citation counts could be correlated to peer judgments (Bayer and Folger, 1966; Garfield, 1970), which are in turn commonly accepted as a way to rank scientific performance (Garfield, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Several journals dedicated to neuroradiology exist; however, neuroradiologic articles are also included in general radiology journals and in radiology subspecialty journals such as those dedicated to pediatric radiology. While there is a growing body of bibliometric analyses in the radiology literature, [4][5][6][7] few studies have focused on neuroradiology topics to date. [8][9][10] We hypothesized that the citation characteristics of a journal are heterogeneous among journal subsections and varying topics.…”
mentioning
confidence: 99%